2018
DOI: 10.3389/fmicb.2018.02823
|View full text |Cite
|
Sign up to set email alerts
|

High Microbial Diversity Despite Extremely Low Biomass in a Deep Karst Aquifer

Abstract: Despite the importance of karst aquifers as a source of drinking water, little is known about the role of microorganisms in maintaining the quality of this water. One of the limitations in exploring the microbiology of these environments is access, which is usually limited to wells and surface springs. In this study, we compared the microbiology of the Madison karst aquifer sampled via the potentiometric lakes of Wind Cave with surface sampling wells and a spring. Our data indicated that only the Streeter Well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 100 publications
3
22
0
2
Order By: Relevance
“…The relative abundances of bacterial and archaeal 16S rRNA gene sequences in the springs were similar to the abundances found in other aquifer studies, and some similar taxa have also been reported previously (41)(42)(43)(44). Proteobacteria and Cyanobacteria composed a large portion of the 16S rRNA gene sequences from all of the Florida springs investigated here.…”
Section: Figsupporting
confidence: 89%
“…The relative abundances of bacterial and archaeal 16S rRNA gene sequences in the springs were similar to the abundances found in other aquifer studies, and some similar taxa have also been reported previously (41)(42)(43)(44). Proteobacteria and Cyanobacteria composed a large portion of the 16S rRNA gene sequences from all of the Florida springs investigated here.…”
Section: Figsupporting
confidence: 89%
“…Field samples were collected from a global set of diverse environments ( Figure 1 ) that were found to contain candidate phyla of Bacteria and Archaea in prior studies ( Rinke et al, 2013 ; Thomas et al, 2013 ; Moser et al, 2015 ; Becraft et al, 2017 ; Hershey et al, 2018 ; Sackett, 2018 ; Sackett et al, 2018 , 2019 ). Immediately after collection, samples were amended with sterile 5% glycerol and 1 mM EDTA (final concentrations) and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial biomass is an important driver of decomposition rates in surface freshwater (Hieber and Gessner, 2002), but the influence on the decomposition can also be more affected by the community composition and enzymatic activity than by the microbial biomass alone (Hieber and Gessner, 2002;Chapin et al, 2011). Nutrient limited caves are known to have high microbial diversity (Barton, 2015;Hershey et al, 2018), this diversity may potentially stimulate the decomposition process inside caves. On the other hand, in caves where invertebrates are more abundant, we expect the decomposition to be stimulated by their physical breakdown of substrates (Chapin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%